Screening of quinoline, 1, 3-benzoxazine, and 1, 3-oxazine-based small molecules against isolated methionyl-tRNA synthetase and A549 and HCT116 cancer cells including an in silico binding mode analysis1. Issue 36 (28th September 2015) - Bharathkumar, Hanumantharayappa; Mohan, Chakrabhavi Dhananjaya; Rangappa, Shobith; Kang, Taehee; Keerthy, H. K.; Fuchs, Julian E.; Kwon, Nam Hoon; Bender, Andreas; Kim, Sunghoon; Basappa; Rangappa, Kanchugarakoppal S.
<x xml:space="preserve">Abstract</x> Elevated activity of methionyl-tRNA synthetase (MRS) in many cancers renders it a possible drug target in this disease area, as well as in a series of parasitic diseases.